Best Results From Yahoo Answers Youtube
From Yahoo Answers
Answers:you don't need to do any algebra. Just replace x by a number, and let y equal the expression you have just written down: let x = 7, so 3/x becomes 3/7 and that's y! (7,3/7) keep doing it. and if you don't want to bother having to reduce fractions to lowest terms, just pick values of x that are not multiples of 3, so you don't have to do any work at all! ( 5, 3/5) (13,3/13) (11, 3/11) (29, 3/29) (89, 3/89) (100, 3/100) etc I hope that now even you, who claim to "suck" at algebra, will say "hey, that's easy!" Sheila Tobias is a sociologist, (NOT a mathematician) who has done research on math anxiety in girls and women, and one of her conclusions is that often that voice in our heads that says 'I'm not good at math" ,along with all the associated negative thoughts, is occupying so much of our minds that we have too little room left in our minds to actually THINK about the math! In some cases, that means that we never even give ourselves a chance to see that a particular problem is not really asking us to do very much at all, because we just assume beforehand that it will be hard and therefore too scary to think about.
Answers:I'm not certain what you're asking so I'll give a couple of different answers. If you're thinking that you should use x=1.5 and substitute into the equation to find y, and then repeat with y=-2 to find x. Basically, I think you're trying to solve two questions. Is that right? If not, skip down to the ************** section and look at the alternative answer. let's use x-1.5 just to start with. Where ever you see x, just write (1.5 * ...); like this. 6x + 3y = 12 6*1.5 + 3y = 12 9 + 3y = 12 (now subtract 9 from both sides) 3y = 3 y = 3 Now try for y = -2 6x + 3y = 12 6x + 3*-2 = 12 6x + -6 = 12 (same as 6x -6 = 12) 6x = 18 (now divide both sides by 6) x = 3 You have your two answers. **************************************** If you're being asked to rewrite the equation in terms of y = or x =, you should write it like this: 6x + 3y = 12 3 divides evenly into each of these so we can simplify the equation. 2x + y = 4 You can now use x = 1.5 or y= -2 and repeat the process used ealier. or if you're being asked to rewrite your equations so you have x = or a y = 2x + y = 4 (subtract 2x from both sides) y = 4 - 2x or y = -2x + 4 2x + y = 4 (subtract y from both sides) 2x = -y + 4 or 2x = 4 - y (divide both by 2 to remove the coeffecient) x = (4 - y)/2 [ there are other ways to write this answer e.g., x = 2 - (1/2)y ] There you have it - two equations a x in terms of y and y in terms of x. I hope these two sections didn't confuse you.
Answers:Its simultaneous equations I think. Use substitution. Firstly number the equations. (i) y=3x+31 (ii) 3x-5y=1 Substitute (i) into (ii), 3x-5(3x+31)=1 Then rearrange to find x. 3x-15x-155=1 -12x=156 x=-13 Substitute x back into the equations to find y. y=3(-13)+31 y=-2 So the answer is (-13,-2)
Answers:18. ( 9, 1) , ( 9, 2) , ( 9, 3) , 20. ( 1 , 10),( 2 , 10),( 3 , 10), 22. (-10, 2), (-10, 2), (-10, 3),